The Impact of Good Corporate Governance and Leverage on Financial Performance of Manufacturing Companies - Herman Ruslim (Atestasi : Jurnal Ilmiah Akuntansi, 2021)
This study aims to examine the impact of effective corporate governance and leverage on the financial performance of manufacturing firms publicly listed on the Indonesia Stock Exchange. This study employs a quantitative research strategy, utilizing various research methods, including normality testing, multicollinearity testing, and heteroscedasticity testing. Additionally, regression analysis is conducted, explicitly employing multiple linear regression analysis, hypothesis testing analysis, and calculating the coefficient of determination. The study's findings indicate a positive and statistically significant relationship between institutional ownership and financial performance. The presence of managerial ownership exerts a favorable and statistically significant impact on a firm's financial success. The company of independent commissioners has been found to have a clear and statistically significant effect on financial performance. The presence of an audit committee has been found to have a favorable and statistically significant impact on financial performance. The utilization of leverage, as indicated by the Debt-to-Asset Ratio (DAR), exhibits a noteworthy and positive effect on the financial performance of an entity. The positive test findings obtained suggest a positive correlation between a firm's leverage and its financial performance, indicating that as the leverage of a company increases, its financial performance is also expected to increase. This positive correlation can arise due to the prevalence of sample companies with a higher proportion of debt in their capital structure than their equity. The concurrent influence of effective corporate governance and leverage on a company's financial success is noteworthy. The financial success of a corporation can be predicted by utilizing many GCG variables, namely independent commissioners, audit committees, institutional ownership, and managerial ownership, together with leverage